Calculation of gamma-ray attenuation parameters for aluminium, iron, zirconium and tungsten - Hiwa Mohammad Qadr (Вопросы атомной науки и техники, 2020)
The purpose of this study was to determine the linear attenuation coefficient, the mass attenuation coefficient, Half Value Layer. Tenth Value Layer and Mean Free Path for four different shielding materials such as aluminium, iron, zirconium and tungsten. By using the gamma radiation energies emitted from ¹⁵²Eu, ²²Na, ¹³⁷Cs, and ⁶⁰Co radioactive sources. For this purpose, the attenuation measurements were performed using NaI (TI) detector. Calculated values of all parameters of the all shielding materials were compared with each other. The results of all presented parameters show that, tungsten has the best radiation shielding compared to other shielding materials. Then, the obtained parameters were compared with the theoretical values.